To Study Gen-Z Perception about Cosmetic Beauty Ayurvedic Brands in Ahmedabad City - Shubham Suthar; Pratiksha Agrawat; Jignesh Vidani (MultiTech Publisher, 2024)
The article deals with the effects of age on the perception of consumers towards Ayurvedic cosmetics, in regard to price, brand reputation, packaging, safety, stability, and social media influence. This work uses a few ideas along with statistical analysis to determine whether or not there is an influence on consumer opinion towards Ayurvedic cosmetics based on age in comparison with non-Ayurvedic variants. According to the study, there does not exist any strong correlation between age or several customers' perceptions. Instead, product's effectiveness, consciousness of the environment, and consciousness of health are viewed to be strongly influencing purchasing behaviour. The study supports a new approach to traditional age-based marketing segmentation and focuses psychographic segmentation, such as sustainability and health. Also, the minor effect of social media advertising efforts on buying choices shows